2013
DOI: 10.1007/s12272-013-0217-0
|View full text |Cite
|
Sign up to set email alerts
|

Isoalantolactone, a sesquiterpene lactone, induces apoptosis in SGC-7901 cells via mitochondrial and phosphatidylinositol 3-kinase/Akt signaling pathways

Abstract: Isoalantolactone, a sesquiterpene lactone, possesses anti-fungal as well as cytotoxic properties. In this study, the effects of Isoalantolactone on cell viability, cell cycle, and apoptosis were investigated in human gastric adenocarcinoma SGC-7901 cells. The results demonstrated that Isoalantolactone induced morphological changes and decreased cell viability. Subsequently, we found that Isoalantolactone induced G2/M and S phase arrest, which was associated with a decrease in the expression level of cyclin B1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…In the present study, SGC7901 cells were treated with doxorubicin, and the rate of apoptosis increased when P-REX2a was knocked down. Bcl-2 and Bax are anti-apoptotic and pro-apoptotic effectors, respectively, and are important regulators in the PI3K/Akt signaling pathway (25). The expression of Bcl-2 was decreased and the expression of Bax was increased in cells transfected with P-REX2a-siRNA compared with the negative control.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, SGC7901 cells were treated with doxorubicin, and the rate of apoptosis increased when P-REX2a was knocked down. Bcl-2 and Bax are anti-apoptotic and pro-apoptotic effectors, respectively, and are important regulators in the PI3K/Akt signaling pathway (25). The expression of Bcl-2 was decreased and the expression of Bax was increased in cells transfected with P-REX2a-siRNA compared with the negative control.…”
Section: Discussionmentioning
confidence: 99%
“…Isoalantolactone has been reported to induce cell death in several human cancer cell lines, such as PANC-1 cells (6), human prostate cancer cells (8), and human gastric adenocarcinoma SGC-7901 cells (9) via cell cycle arrest and induction of apoptosis. In line with previous reports, we found that isoalantolactone arrested the cell cycle at the S and mainly the G2/M phase in U2OS cells.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Khan et al showed that isoalantolactone did not exert any acute or chronic cytotoxicity in mouse liver and kidney (6). Although there are a few reports on the anticancer activities of isoalantolactone (6)(7)(8)(9)(10), there is no report available on the anti-osteosarcoma effect of isoalantolactone.…”
Section: Introductionmentioning
confidence: 99%
“…Isoalantolactone inhibits phosphorylation of PI3K/Akt on SGC-7901 cells (98), and alantolactone seems to induce detoxifying enzymes via activation of the PI3K and JNK signaling pathways (89). In cervical carcinoma HeLa cell line, oridonin may suppress constitutively activated targets of phosphatidylinositol 3-kinase (Akt, FOXO, and GSK3; ref.…”
Section: Growth Factors and Their Receptors Family Pathwaymentioning
confidence: 99%